Tubeimoside I promotes angiogenesis via activation of eNOS-VEGF signaling pathway. (1st March 2021) - Yang, Xiyang; Li, Xingbing; Luo, Minghao; Guo, Yongzheng; Li, Chang; Lv, Dingyi; Cheng, Zhe; Huang, Longxiang; Shang, Fei-Fei; Huang, Bi; Shen, Jian; Luo, Suxin; et al.
Abstract: Ethnopharmacological relevance: Tubeimoside I (TBM) is a triterpenoid saponin purified from tubeimu (tuber of Bolbostemma paniculatum (Maxim.) Franquet). In traditional Chinese medicine, tubeimu had been used to treat acute mastitis, snake bites, detoxication, inflammatory diseases, and tumors for over 1000 years. Aim of the study: This study aimed to investigate whether TBM could promote angiogenesis and how to promote angiogenesis. Materials and methods: In vivo, the pro-angiogenic effects of TBM were examined using the hindlimb ischemia model. After the ischemia operation, 1 mg/kg/day TBM was given via intraperitoneal injection for 28 days and the recovery of blood flow was monitored by Doppler scanner every 7 days. The capillary density in gastrocnemius muscle was detected by immunofluorescence. Expression of related proteins were determined by western blotting. In vitro, the pro-angiogenic effects of TBM on HUVECs were examined by Cell Counting Kit-8, scratch assay, endothelial cell tube formation assay and western blotting. Results: TBM improved recovery from hindlimb ischemia in C57BL/6 mice. TBM promoted endothelial cell viability, migration and tube formation in HUVECs. TBM could activate eNOS-VEGF signaling pathway by enhancing expression of eNOS. And TBM's pro-angiogenesis effects could be abolished by L-NAME (an inhibitor of eNOS). Conclusions: TBM promoted angiogenesis via the activation of eNOS-VEGF signaling pathway and TBM could be a novel agent for therapeutic angiogenesis in ischemic diseases. Graphical abstract: Image 1